2021
DOI: 10.55215/pedagogia.v13i2.4498
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Reading from Students’ Perspective

Abstract: Extensive reading is broadly known as reading for enjoyment and is beneficial for EFL students. However, nowadays, the growth of technology has become a matter for students to be reading less than they should be. Thus, this research focused on the online extensive reading as the course program the students had experience in Pakuan University to find out their perspective. The respondents were 15 students from sixth-semester students who had experienced the Online Extensive Reading subject. The research was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The absence of extensive reading in the Latin classrooms that I observed during my PGCE despite its benefits, and the lack of research into extensive reading in Latin classrooms in general, prompted me to choose this topic for my research project. Due to it being a small-scale research project, I decided to look at student perspectives of extensive reading, as this is not typically the focus of extensive reading research (Abrar et al, 2021) and it was more attainable for the time I had allowed.…”
Section: The Researchmentioning
confidence: 99%
“…The absence of extensive reading in the Latin classrooms that I observed during my PGCE despite its benefits, and the lack of research into extensive reading in Latin classrooms in general, prompted me to choose this topic for my research project. Due to it being a small-scale research project, I decided to look at student perspectives of extensive reading, as this is not typically the focus of extensive reading research (Abrar et al, 2021) and it was more attainable for the time I had allowed.…”
Section: The Researchmentioning
confidence: 99%
“…It is known that an extensive reading program is able to improve second language ability, improve motivation and self-confidence and self-image as an EFL learner (Yılmaz et al, 2020). Then, the research related to students' perception on extensive reading revealed they have positive opinions related to extensive reading because it provides huge benefits for them such as vocabulary gain, reading interest, and reading comprehension (Abrar et al, 2021). However, there is rarely any research which explicitly explains how extensive reading success was reached and the things which must be done by educators to maintain students' reading habit after the program is ended.…”
Section: Introductionmentioning
confidence: 99%